CHEMICAL COMPOSITION AND PHARMACOGNESTIC STUDY OF CRUDE PLANT EXTRACT OF VERNONIA ELAEAGNIFOLIA - U.S. KHANDEKAR; S.K. TIPPAT; R.A. GHONGADE; K. DUDHE (International Journal of Pharma and Bio Sciences, 2015)
In the present investigation, a field experiments aimed at evaluating phytoconstituents, chemical composition, antioxidants and antimicrobial activity of V. elaeagnifolia leaf. The gas chromatography coupled to mass spectroscopy GC-MS, eight compound were determined, the major compounds identified in the crude plant extract were Phorbol12,13- dihexanolate(19.84%), Cyclopropal (3,4) benz (1,2,e) azulene- (16.55%), Mibemycin, b,13- choro-5-demethoxy-28-epoxy-5(hydroxyimino)-25-(1-methylethy)(15.12%).The timicrobial susceptibility results obtained in this work revealed that the extraction yield of the different extraction solvents used was correlated with the antimicrobial activity observed. Of the isolates tested, only 3(MEE and EAE) revealed susceptibly to the extracts, with DMSOE revealing the highest susceptibility. DPPH radical scavenging activity of Vernonia leaf extract with ascorbic acid as reference where the IC50 value for the Vernonia extract (IC50 = 3259 µg/ml) and IC50 value was said to be moderate as compared to standard (IC50= 2782 µg/ml).